Unlocking Better Sleep and Stress Relief: The Power of Ashwagandha (Withania somnifera) Supplementation – A Literature Review - Grabowski, Wojciech Krzysztof; Karoń, Karolina Anna; Karoń, Łukasz Mikołaj; Zygmunt, Anna Ewa; Drapała, Grzegorz; Pedrycz, Emilia; Pedrycz, Daria Katarzyna (Quality in Sport, 2024)
Ashwagandha (Withania somnifera) is known for its adaptogenic properties, helping the body manage stress from various sources. This review, based on 23 studies, evaluates Ashwagandha’s effectiveness in enhancing sleep quality and reducing stress. The herb’s bioactive compounds modulate stress responses and neurotransmitter systems, contributing to improved mental and physical resilience. The studies consistently show that Ashwagandha supplementation (250 to 600 mg daily for 4 to 12 weeks) significantly improves sleep quality, latency, and efficiency. These effects are largely due to the modulation of the hypothalamic-pituitary-adrenal (HPA) axis, cortisol reduction, and enhancement of GABAergic and serotonergic pathways. Ashwagandha also extends total sleep time in various populations, including healthy adults and the elderly. In addition to enhancing sleep, Ashwagandha reduces stress by lowering cortisol levels and modulating neurotransmitter systems. Numerous studies highlight its role in alleviating anxiety and improving mental well-being. However, some studies report gastrointestinal issues and potential interactions with medications, necessitating caution and consultation with healthcare providers. This review synthesizes current research, identifies trends, and highlights gaps in the literature, contributing to a better understanding of Ashwagandha’s role in modern health practices. Given the challenges of sleep disorders and stress-related conditions, Ashwagandha shows promise as a natural remedy, particularly for those with anxiety or chronic stress. Future research should focus on understanding the underlying mechanisms, ensuring long-term safety, and standardizing supplement quality to strengthen its therapeutic applications.